Genetic variants on 17q21 are associated with ankylosing spondylitis susceptibility and severity in a Chinese Han population. (November 2013) - Qiu, R; Zhang, H; Zhao, H; Li, J; Guo, C; Gong, Y; Liu, Q
<x xml:space="preserve">Abstract</x> Objectives: The aim of this study was to test whether orosomucoid like 3 (ORMDL3) and 17q21 variants are associated with susceptibility to ankylosing spondylitis (AS) in a Chinese population. Method: A total of 753 unrelated AS patients and 1120 ethnically matched healthy controls were recruited. Seven single nucleotide polymorphisms (SNPs: rs7216389, rs12603332, rs12936231, rs9303277, rs11557467, rs1007654, and rs17608925), which were selected from chromosome 17q21 containing the genes ORMDL3, GSDMB, ZPBP2, and IKZF3, were genotyped by the Taqman SNP genotyping assay. Results: Five of the SNPs (rs7216389, rs12603332, rs12936231, rs9303277, and rs11557467) were associated with AS (all p ≤ 0.01), especially in males (all p < 0.001). Of these, rs7216389, rs12603332, rs12936231, and rs11557467 were strongly associated with severity of the disease based on radiographic findings (p < 0.05). Conclusions: Our study confirmed that variants in chromosome 17q21 are significantly associated with AS in a Chinese Han population.